2019
DOI: 10.1126/science.aaw9247
|View full text |Cite
|
Sign up to set email alerts
|

The geologic history of seawater oxygen isotopes from marine iron oxides

Abstract: The oxygen isotope composition (δ18O) of marine sedimentary rocks has increased by 10 to 15 per mil since Archean time. Interpretation of this trend is hindered by the dual control of temperature and fluid δ18O on the rocks’ isotopic composition. A new δ18O record in marine iron oxides covering the past ~2000 million years shows a similar secular rise. Iron oxide precipitation experiments reveal a weakly temperature-dependent iron oxide–water oxygen isotope fractionation, suggesting that increasing seawater δ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 170 publications
7
45
1
1
Order By: Relevance
“…This relative relationship between seawater and more 18 O-depleted meteoric waters is significant here, as it has been suggested that the δ 18 O of seawater (0‰ at present 23 ) may have changed through time, perhaps being as low as −10‰ in the Archaean 25 . Newly reported iron oxide δ 18 O records, which are insensitive to temperature, convincingly support that seawater was lower in the past, having a δ 18 O at near −8‰ by around 2.0 Ga 48 . Palaeoproterozoic seawater appears to be faithfully recorded in Kazput carbonate that is, as mentioned previously, on the order of 10‰ lower than modern carbonates but comparable to carbonates from around 2.3 Ga.…”
Section: Resultsmentioning
confidence: 83%
“…This relative relationship between seawater and more 18 O-depleted meteoric waters is significant here, as it has been suggested that the δ 18 O of seawater (0‰ at present 23 ) may have changed through time, perhaps being as low as −10‰ in the Archaean 25 . Newly reported iron oxide δ 18 O records, which are insensitive to temperature, convincingly support that seawater was lower in the past, having a δ 18 O at near −8‰ by around 2.0 Ga 48 . Palaeoproterozoic seawater appears to be faithfully recorded in Kazput carbonate that is, as mentioned previously, on the order of 10‰ lower than modern carbonates but comparable to carbonates from around 2.3 Ga.…”
Section: Resultsmentioning
confidence: 83%
“…Siderite isolated from these bands yields clumped isotope temperatures of 37-45°C and calculated water oxygen isotope values of -8 to -6‰ (VSMOW). Though preliminary, this is consistent with previous estimates of seawater temperature from chert [3] and δ 18 O value from iron oxides [4]. New data from both siderite and whole carbonate measurements will be presented and reconciled with models of Gunflint ironstone diagenesis.…”
supporting
confidence: 84%
“…In addition, clumped isotopes show little change in Phanerozoic d 18 O seawater [e.g., (235)]. Alternatively, O isotopes in iron oxides since 2 Ga ago suggest a secular increase in d 18 O seawater (236).…”
Section: Physical and Geochemical Evidence Of A Moderate Archean Climatementioning
confidence: 99%